Spécificités de la conservation muséale de fragments d'environnements d'art brut - Mélanie Paul-Hazard (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This study is about sculptures coming from an outsider art environment in Normandy, now conserved in the LaM. The study pointed out specific conservation issues linked to this type of spontaneous creation and particularly to objects that were museified after a site’s destruction. Prior to the restoration, we carried out an documentary work on A. Hardy as well as a detailed material study of one sculpture, completed with a reflection about its outdoor exhibition.